Identifying Students' Pre-Classroom Behaviors in a Flipped Learning Environment - Daniel Febrian Sengkey; Sary Diane Ekawati Paturusi; Alwin M. Sambul (Fakultas Teknik Universitas Sam Ratulangi, 2019)
Advancements in Information Technology have lead the world to new ways of life including in the education field. Nowadays we have various types of computer and Internet-assisted learning. With the booming of blended learning, here comes the flipped classroom environment, where students are expected to learn even before the conventional class meetings started. In this study, we address the question of how students behave toward various learning materials packaged in 3 types of media: text and images, slide shows with audio narration, and slide shows with the appearance of the lecturer. Based on our samples the findings are surprising: some students never made access before the class; and on the other hand, the text-and-image-based learning materials have the highest number of pre-classroom access.